From Dayung to DIY: Locally Constructed Maritime Technologies in Coastal Philippine Communities - Balili, Jr, Enrique E. (Future Science / FSH-PH Publications, 2025)
This study examines the shift from the traditional dayung - a communal boat-launching practice steeped in cooperation and shared labor—to individually crafted and self-reliant (“do-it-yourself)” launching innovations among fisherfolk in the Sogod Bay, Leyte, Philippines. The research uncovers various adaptive practices using semi-structured interviews and thematic analysis, including bamboo sliding mechanisms, detachable wheels, and makeshift floating docks. These locally engineered solutions reflect how coastal communities respond to evolving social, economic, and environmental constraints while preserving core aspects of cultural identity. Anchored in the Social Construction of Technology (SCOT) framework, the findings illustrate how fisherfolk actively reinterpret available resources and repurpose indigenous knowledge to meet livelihood demands, highlighting the community’s agency in shaping technology from the margins. This socio-technical evolution underscores the interplay between tradition and innovation, revealing how cultural resilience informs sustainable practices in small-scale fisheries.